Heterogeneity of Falls Among Older Adults: Implications for Public Health Prevention - Kelsey, Jennifer L. (American Public Health Association, 2012)
Objectives. We examined risk factors for falls among older people according to indoor and outdoor activity at the time of the fall and explored risk factors for seriously injurious falls. Methods. Data came from MOBILIZE Boston, a prospective cohort study of 765 community-dwelling women and men, mainly aged 70 years or older. Over 4.3 years, 1737 falls were recorded, along with indoor or outdoor activity at the time of the fall. Results. Participants with poor baseline health characteristics had elevated rates of indoor falls while transitioning, walking, or not moving. Healthy, active people had elevated rates of outdoor falls during walking and vigorous activity. For instance, participants with fast, rather than normal, gait speed, had a rate ratio of 7.36 (95% confidence interval [CI] = 2.54, 21.28) for outdoor falls during vigorous activity. The likelihood of a seriously injurious fall also varied by personal characteristics, activity, and location. For example, the odds ratio for serious injury from an outdoor fall while walking outside compared to inside a participant’s neighborhood was 3.31 (95% CI = 1.33, 8.23). Conclusions. Fall prevention programs should be tailored to personal characteristics, activities, and locations.